Antimicrobial Susceptibility of Ehrlichia phagocytophila - Horowitz, Harold W. (American Society for Microbiology, 2001)
Human granulocytic ehrlichiosis is a recently described disease caused by an obligate intracellular gram-negative organism recently named Ehrlichia phagocytophila. To expand our knowledge of the susceptibility of E. phagocytophila, we tested six New York State isolates for susceptibility to 12 antimicrobials using an HL-60 cell culture system. All of the isolates were susceptible to doxycycline (MIC, ≤0.125 μg/ml; minimum bactericidal concentration [MBC], 0.125 to 0.5 μg/ml), rifampin (MIC, ≤0.125 μg/ml; MBC, ≤0.125 μg/ml), ofloxacin (MIC, ≤2 μg/ml; MBC, ≤2 μg/ml), levofloxacin (MIC, ≤1 μg/ml; MBC, ≤1 μg/ml), and trovafloxacin (MIC, ≤0.032 μg/ml; MBC, ≤0.032 μg/ml). Isolates were uniformly resistant to amoxicillin, ceftriaxone, erythromycin, azithromycin, clarithromycin, and amikacin. For one strain, the MBC of chloramphenicol was ≤8 μg/ml. These data suggest that quinolone antibiotics and rifampin may be alternative agents for patients with intolerance to tetracyclines.